Fruit orchard viewed from indoors - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows the view of a what appears to be a fruit orchard from indoors. The window of the house frames the scene. The trunk of a palm tree sits left of center, and palm trees border the property.